Atomic Salvation: A Case for Nuclear Planetary Defense. Issue 1 (2nd January 2020) - Doboš, Bohumil; Pražák, Jakub; Němečková, Marie
ABSTRACT: Asteroid and comet collisions present low-chance, high-impact risks for the Earth. As such, it is unlikely that space powers will invest into capabilities aiming at the development of new deflection technologies leaving planetary defense with two readily available methods – kinetic impactor and nuclear warhead. Legally and normatively, the use of a nuclear device in outer space is in the current state of affairs forbidden. In the case of an emergency with an impending impact, such an approach is needed. This article suggests that establishment of an exception in international space law strengthens the nuclear regime while allowing for an effective deflection in the space domain if the need arises.